HER2-low non-metastatic breast cancer in Qatar—a nationwide retrospective cohort study to evaluate the response to neoadjuvant chemotherapy: a real-world analysis - Kardousha, Ahmed; Shehada, Wafaa; Basha, Ahmed; Nasser, Sahar; El Mistiri, Mufid; Hamad, Anas; Bujassoum Al-Bader, Salha; Elazzazy, Shereen (Frontiers in Oncology, 2024)
Globally, breast cancer is the most prevalent cancer and one of the leading causes of cancer-related death among women. HER2-low breast cancer represents a recently identified molecular category within breast cancer characterized by tumors displaying only slight overexpression of HER2 or lacking gene amplification. To illustrate, HER2-low tumors typically have an IHC (immune histochemistry) score of 1+ or 2+ with negative amplification. Nonetheless, recent findings indicate that even a slight amplification of HER2 could notably influence both therapeutic responses and prognostic outcomes. Our study aims to unveil the impact of HER2-low expression on the response to anthracycline and taxane-based neoadjuvant chemotherapy (NACT) in comparison to the HER2-negative group in non-metastatic breast cancer. This is a retrospective cohort study. All patients’ profiles with non-metastatic, HER2-low, and HER2-negative breast cancers who were administered neo-adjuvant chemotherapy and had surgery performed within the period spanning from 1 January 2018 to 30 August 2022 were enrolled. HER2-positive breast cancer patients were excluded. The evaluation of patients’ responses was conducted through the examination of surgical pathology reports to compare the two study groups (HER2-low and HER2-negative). The primary objective was evaluating the response to NACT comparing the objective response rate (ORR) in each of the two groups of HER2-low and HER2-negative patients. The total number of patients included was 262 patients; the majority were HER2-low 89% (233/262) vs. 11% (29/262) HER2-negative. An ORR (complete and partial response) to NACT was shown in 71% (185/262) of all patients. The ORR was similar in both groups, 70% (164/233) in the HER2-low group vs. 73% (21/29) in the HER2-negative group, with a statistical difference, OR: 1 (95% CI: 0.8–1), p-value 0.8. Similarly, the pathological complete response (pCR) rate was the same in both study groups at 14%, OR: 0.7 (95% CI: 0.2–3), p-value: 0.6. Interestingly, patients with hormone-positive tumors across both study groups had a higher response rate compared to hormone-negative patients. In the HER2-low cohort, the ORR was higher in patients with hormone-positive tumors in comparison with those with hormone-negative tumors [73% vs. 27%, OR: 0.8 (95% CI:0.8–1), p-value: 0.001]. Comparatively, in the HER2-negative cohort, ORR was also higher in patients with hormone-positive tumors compared to hormone-negative tumors [52% vs. 48%, OR: 2 (95% CI: 1–5), p-value: 0.05]. Subsequently, the ORR of all hormone-positive tumors with a positive outcome (CR or PR) was assessed categorizing the patients based on their HER2 expression. Concerning patients who expressed partial response (N = 115), a statistically significant difference was observed in HER2- low hormone-positive tumors as opposed to HER2-negative hormone-positive tumors [90% vs. 10%, OR: 0.7 (95% CI: 0.5–0.9), p-value: 0.001]. Remarkably, all patients with complete responses were from the HER2-low cohort. Our findings demonstrated a significant influence of HER2-low expression on the response to neoadjuvant chemotherapy among patients with hormone-positive HER2-low breast cancer within the studied cohort. Further studies are needed to evaluate the influence of hormonal expression on the response rate to NACT in the HER2-low patients in our population.